The Adaptation Characteristics of Traditional Dwelling in Bawean to The Environmental Condition at Indonesian Archipelago - FX Teddy Badai Samodra; Andy Mappajaya; Rabbani Kharismawan (Unika Soegijapranata Semarang, 2019)
The Indonesian archipelago has typical traditional dwelling richness on every island. In island city, Bawean, the wind effect becomes very critical to the identification of environmental adaptation of its dwelling. The aim of this study was to identify the adaptation characteristics of traditional dwelling to the environmental archipelago condition of Bawean island. In this study, two main dwellings as references are the traditional houses, Bangsal or Limas and Barn, Durung. Generally, this research involves two major steps as follows: (1) Identification and specification phase (field observations, measurements) of the characteristics of building performance, (2) Simulation phase of the thermal performance of traditional house (using Ecotect Analysis and CFD Programs). This results highlighted that the houses performance is not optimum, both in spreads and compact orders. Meanwhile, Durung has better performance, only 17% of the samples are in discomfort condition (spread or compact). The optimum condition is achieved when the settlement spread out, otherwise uncomfortable when it is in the dense environment. The houses in daytime conditions are in the discomfort conditions and lower cooling load, while the night-time conditions are in the quadrant of optimum conditions, comfort, and low cooling load.